Epidemiological analysis of pulmonary tuberculosis and extra-pulmonary tuberculosis in Saudi Arabia: a cross-sectional study - Ahmad Almatroudi (All Life)
Tuberculosis (TB) is a serious disease that affects people worldwide, including in Saudi Arabia. The study analyzed the frequency of diagnosed TB cases, age-specific incidence rate, year of diagnosis, and prevalence of TB in Saudi Arabia from 2014 to 2020. Based on the National Tuberculosis Program (NTP) data, 21,120 patients were diagnosed with TB. The mean incidence rate of pulmonary TB and extra-pulmonary TB was approximately 6.92 and 2.33 per 100,000 population, respectively. The highest age-specific incidence rate was observed in the 25–35 year age group. The non-Saudi population (11,086 cases; 52.50%) was significantly more affected by both types of TB compared to the Saudi population (10,034 cases; 47.50%). The male population of Saudi and non-Saudi was significantly more affected by both types of TB. The highest overall mean incidence rate per 100,000 population was observed in the Jeddah and Jazan regions. The study's findings may have implications for supporting public health interventions and implementing a more effective TB control strategy program in Saudi Arabia. It suggests that immigrants from TB-endemic countries and religious visitors from high-risk countries should undergo pre and post-arrival screening for TB to reduce its incidence.